Cambridge advanced learner's dictionary - McIntosh, Colin (Cambridge University, 2013)
A fully updated edition of the best-selling Cambridge Advanced Learner's Dictionary. This edition is ideal for advanced (C1-C2) learners of English and contains up-to-date vocabulary, including words from the areas of technology, media, language, society, and lifestyle, plus important words for academic study. With over 140,000 words, phrases, meanings, and examples, hundreds of pictures and illustrations, clear definitions and a new 'Focus on Writing' section, the dictionary is perfect as a reference tool and as a study companion. Informed by the Cambridge International Corpus and correlated to English Vocabulary Profile, it is also ideal for exam preparation. The CD-ROM contains the complete dictionary and recordings in British and American English; CD-ROM for Windows and MAC; For Windows XP/Vista/7/8 and Mac OSX 10.5-10.8--CD-ROM cover